Political Capital of Legislative Member Ahmad Yamin in the Legislative Elections for the 2019-2024 Period in Banyuasin - SUMAYYAH, SITI (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research is entitled